2015
DOI: 10.1007/s10973-015-4661-6
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpies of immersion in benzene, cyclohexane and water of granular activated carbons prepared by chemical activation with solutions of MgCl2 and CaCl2

Abstract: Granular-type activated carbons were prepared from African palm shells (Elaeis guineensis) by chemical activation with aqueous solutions of MgCl 2 and CaCl 2 at concentrations of 3, 5 and 7 % w/v, at temperatures between 773 and 1073 K. The textural parameters were obtained from N 2 adsorption isotherms of the prepared activated carbons. The textural parameters included the surface area and pore volume, with values between 10 and 501 m 2 g -1 and 0.01 and 0.29 cm 3 g -1 , respectively. Enthalpic characterisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In regards to the hydrophobic factor, it is observed that the treatments to which the GAC activated carbon was subjected generated a decrease in the hydrophobicity of the material, due to the fact that its chemical surface was enriched by oxygenated and nitrogenous groups which interact with the molecules of water increasing the affinity of activated carbon with water. In this sense, it is determined that the magnitude of the immersion enthalpy of the three samples in water, correlate with the acidity of the material, as a result, an increase in this parameter with the acidity of the solids is found, as it has been shown in other studies (Stoeckli and Centeno, 1997 ; Silvestre-Albero et al, 2001 ; Acevedo et al, 2015 ).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…In regards to the hydrophobic factor, it is observed that the treatments to which the GAC activated carbon was subjected generated a decrease in the hydrophobicity of the material, due to the fact that its chemical surface was enriched by oxygenated and nitrogenous groups which interact with the molecules of water increasing the affinity of activated carbon with water. In this sense, it is determined that the magnitude of the immersion enthalpy of the three samples in water, correlate with the acidity of the material, as a result, an increase in this parameter with the acidity of the solids is found, as it has been shown in other studies (Stoeckli and Centeno, 1997 ; Silvestre-Albero et al, 2001 ; Acevedo et al, 2015 ).…”
Section: Resultssupporting
confidence: 59%
“…In Figure 4A the thermogram of the immersion of the activated carbon in benzene is shown, this non-polar molecule does not chemically interact with the solid, the molecules of this liquid enter the carbonaceous structure, accessing the porosity and forming a layer on the solid and therefore the energy associated with the interaction process is directly related to the available surface area in porous materials (Acevedo et al, 2015 ). On the other hand, in Figure 4B , it can be observed that water due to it polar nature interacts mainly with the oxygenated surface groups located at the polar sites at the edges of the graphene layers, because it allows to evaluate the polarity and hydrophobicity of the surface of a solid.…”
Section: Resultsmentioning
confidence: 99%
“…Immersion calorimetry has been frequently used for PSD determination of microporous materials. [13,14] It has also been used to monitorp orosity modification, [10,15] polar site adsorption enthalpy, [16][17][18][19][20] and surface adsorption-site energy distribution. [6,[21][22][23] When using polar fluids, the immersion enthalpy dependss trongly on the surface chemistry and polarity of the surfaceg roups.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, in this research, five experimental determinations were made between the liquid and each FB sample, and average values of the immersion enthalpy were considered. For the adsorbents prepared in this work, FB850-3, FB850-3C, FB850-3N, FB850-3Na, and FB850-3Fe, the following liquids with different molecular diameter: water 0.28 nm, methanol 0.43 nm, t -butanol 0.60 nm, α-pinene 0.70 nm, benzene 0.37 nm, and dichloromethane 0.33 nm. ,, With these molecules the immersion enthalpies were determined. To make the calorimetric blanks additional experiments were carried out using double-distilled and deionized water.…”
Section: Methodsmentioning
confidence: 99%